Threshold between mechanical and thermal breakup of river ice cover - Beltaos, Spyros (Cold Regions Science and Technology, 2003)
Keywords: Ouvrage_Collectif_Numéro1

Social Vulnerability to Environmental Hazards - Cutter, Susan L.; Boruff, Bryan; Shirley, W. Lynn (Social Science Quarterly, 2003)
County-level socioeconomic and demographic data were used to construct an index of social vulnerability to environmental hazards, called the Social Vulnerability Index (SoVI) for the United States based on 1990 data. Copyright (c) 2003 by the Southwestern Social Science Association.